Students' Capability In Understanding Descriptive TextAt The Second Year Of SMP N 1 Juwangi Boyolali In 2012/2013 Academic Year - Setiyani., Dinar; , Drs. Sigit Haryanto, M.Hum; , Siti Fatimah, S.Pd, M.Hum (2013)
understanding descriptive text at the second year of SMP N 1 Juwangi Boyolali (2) to describe the problems faced by the second year students in understanding descriptive text, and (3) to describe the causes of problems faced by the second year students in understanding descriptive text. The study was done in SMP N 1 Juwangi Boyolali. As the sample the writer took 36 students at VIIIC class.The writer conducted treatment to the students in the form of the test. The type of the test is multiple choice with four option and consist of 50 items. After collecting the data and analyzing them by using the formula, the writer described the result of the study. The writer found that the capability of the students in understanding descriptive text can be devided into four level mastery, they are (1) poor level is about 19,44% (7 students), (2) fair level is about 27,78% (10 students) (3) good level is about 50,00% (18 students), and (4) excellent level is about 2,78% (1 student). The problems faced by the students in understanding descriptive text are (1) understanding in looking main idea of the text (2) understanding in looking detail information of the text (3) understanding vopcabulary. The causes of the problems faced by the students are (1) the teacher is less in giving variation in teaching reading passage. (2) the students' vocabulary and grammar are still limited because several students have not habit to develop their reading skill individually and there is no supported facilities to develop the teaching learning process. In conclusion, the students' capability in understanding descriptive text at SMP N 1 Juwangi Boyolali is good.